What Is the Expected Return on a Stock? - MARTIN, IAN W. R.; WAGNER, CHRISTIAN (Journal of Finance, 2019)
ABSTRACT We derive a formula for the expected return on a stock in terms of the risk‐neutral variance of the market and the stock's excess risk‐neutral variance relative to that of the average stock. These quantities can be computed from index and stock option prices; the formula has no free parameters. The theory performs well empirically both in and out of sample. Our results suggest that there is considerably more variation in expected returns, over time and across stocks, than has previously been acknowledged.